PERAN KOMUNIKASI SEBAGAI MITIGASI STIGMATISASI COVID 19 - Felisianus Efrem Jelahut (Fakultas Dakwah dan Komunikasi, 2020)
This study provides an understanding of the role of communication to reduce the stigma of the coronavirus in Indonesian society. The research method used is qualitative with a literature study approach. The results of the study revealed that stigmatization is a communication problem so that the form of two-way communication or dialogue has a role in reducing the stigma. Discussion can be made between fellow citizens and also against the Indonesian government.